Desenvolvimento de uma aplicação web e um aplicativo mobile para o controle da recuperação do treinamento físico através da Total Quality Recovery - Oltmann, Cláudio (2018)
The knowledge about the sports training has advanced in recent times, however, athletes, coaches and scientists still have a lot of questions regarding the ideal moment to apply a new load of training and the necessary time to the recovery of the athletes in order to allow the control of the undesirable adaptations and avoiding the states of tiredness and overtraining. The goal of the present study was to develop and validate a web mobile app to monitor and evaluate the recovery of the training loads on athletes of different sports. It consists on a tranversal descriptive quantitative applied research divided into 4 stages: elaboration and development of the web application and of the mobile app, validation of the content of the web application and of the mobile app along with the area specialist teachers and a pilot study to test the application, where was evaluated the recovery of the athletes through the indicators of the Total Quality Recovery (TQR per and TQR act) on 105 athletes of the group modalities of masculine futsal under 17 category and masculine soccer of the under 12, 13, 14 and 15 categories. The application allows the monitoring of the TQR and can be accessed on the website (www.e-trimp.com) or by the app available for the android system. On the specialist teachers and professionals’ evaluation, 58% of the answers given to the system on the 14 evaluated items were rated as “Excellent”, 34% as “Very good” and 8% as “Good”. The pilot study proved to be important to the system testing, allowing the longitudinal monitoring of the recovery perception (TQR per) and the recovery variables (feeding and hydration, sleep and recovery, relaxation and emotional support, stretching and active recovery), generating basic statistic descriptive summaries, as well as charts of the recovery of the training sessions, the training cycles and even the whole season allowing the immediate intervention or the adjustment of periodization. We have concluded that the use of this technology eliminates a geographic and temporal barrier regarding the management of the training sessions and it can proved to be effective for the collection of important data about the athletes’ recovery, helping the prevention of injuries and the overtraining.